Peranan Dinasti Abbasiyah Terhadap Peradaban Dunia - Iqbal, Iqbal (Jurnal Studi Agama dan Masyarakat, 2015)
Abbasiyah empire is which one empire in Islam. In History, Abbasiyah empire is top empire, so we called it as